UW Washington County Collegiate Rocket Launch Proceeding Paper - Gawrys, Joseph J; Flynn, Shane; Read, Max; Grauden, Kota; Sawatzke, Vanessa (Proceedings of the Wisconsin Space Conference, 2019)
Our team participated in the 2018 WSGC collegiate rocket launch competition. Our rocket design was a 3 inch diameter, 80 inch length, 3 finned rocket that used an Aerotech I600R motor. In addition to having a successful launch, our goal was to capture a 360 degree photograph using a Samsung Gear 360 camera. We used a modified umbrella that houses the camera on it’s handle. As the rocket descends, the weight distribution of the umbrella causes it to land nearly handle side up, thus taking a clear 360 picture above the grass. A Rocksim flight simulation gave a predicted altitude of 3400 ft and a predicted maximum acceleration of 714 ft/s2.